2009
DOI: 10.1071/ea07071
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high stocking rates on milk production from dryland and irrigated Mediterranean pastures

Abstract: An experiment using herds of ~20 cows (farmlets) assessed the effects of high stocking rates on production and profitability of feeding systems based on dryland and irrigated perennial ryegrass-based pastures in a Mediterranean environment in South Australia over 4 years. A target level of milk production of 7000 L/cow.year was set, based on predicted intakes of 2.7 t DM/cow.year as concentrates, pasture intakes from 1.5 to 2.7 t/cow.year and purchased fodder. In years 1 and 2, up to 1.5 t DM/cow.year of purch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
5
21
1
Order By: Relevance
“…The regression equation derived from these data indicates that as comparative SR increases from 60 to 100 kg LW/t DM, annual pasture utilisation increases from 66 to 85%, with an average increment rate of 4.6% for every 10 kg LW/t DM of increment in comparative SR. In contrast, systems that fed concentrates in farmlet studies in the USA (Fales et al 1995) and Australia (Valentine et al 2009) showed low or nil reduction in pasture intake and pasture utilisation at higher SR because SR and supplementation per hectare were both increased simultaneously in these studies. However, even though comparative SR was not reported in these two studies, it can be inferred that comparative SR was similar across treatments in both studies.…”
Section: Herbage Utilisation and Milk Productionmentioning
confidence: 72%
See 2 more Smart Citations
“…The regression equation derived from these data indicates that as comparative SR increases from 60 to 100 kg LW/t DM, annual pasture utilisation increases from 66 to 85%, with an average increment rate of 4.6% for every 10 kg LW/t DM of increment in comparative SR. In contrast, systems that fed concentrates in farmlet studies in the USA (Fales et al 1995) and Australia (Valentine et al 2009) showed low or nil reduction in pasture intake and pasture utilisation at higher SR because SR and supplementation per hectare were both increased simultaneously in these studies. However, even though comparative SR was not reported in these two studies, it can be inferred that comparative SR was similar across treatments in both studies.…”
Section: Herbage Utilisation and Milk Productionmentioning
confidence: 72%
“…In this experiment, the grazing pressure at the higher SR was not so extreme as to cause detrimental effects on pasture accumulation, and may have allowed pastures to remain close to their optimum herbage mass. In contrast, in an experiment exploring the effect of SR (2.5, 2.9, 3.3, 3.6 and 4.1 cows/ha) on the dairy system, Valentine et al (2009) reported no effect of SR on pasture production. However, in the latter experiment, cows were fed supplements and pasture consumed represented less than 34% of the diet in all SR treatments in dryland farmlets.…”
Section: Pasture Productionmentioning
confidence: 82%
See 1 more Smart Citation
“…The biological effects of increased overall farm SR on milk production per hectare observed within our study are consistent with previous findings and further substantiate the potential for increased biological efficiency within higher-SR grazing systems. Similar to both Valentine et al (2009) andFariña et al (2011), SR had no significant effect on net herbage accumulation but, as a consequence of the increased efficiency of herbage removal and increased grazing severity at higher SR, resulted in increased grazed grass utilization. Both Baudracco et al (2010) and McCarthy et al (2011) have previously likened an increase in SR to a reduction in daily herbage allowance.…”
Section: Discussionmentioning
confidence: 70%
“…Other examples of mostly small farmlets used in research, especially in the dairy industry, have been reported for: a replicated experiment exploring dairy cow stocking rates over two grazing seasons in North America (Fales et al 1995); investigations of nitrogen cycling on four unreplicated, selfcontained farmlets of 6.5 ha with each containing 16 randomly allocated paddocks in New Zealand (Ledgard et al 1999); a study of automated milking on a 9.2-ha farmlet for which paddock layout details have been provided (Jago et al 2007); unreplicated systems studies in Queensland dairy research where five different 20-cow systems were run under research station conditions (Lowe 2007); two 6-ha farmlets studying the effects of hay or silage conservation on the Ellinbank research farm in Victoria (Thomas and Mathews 1991); and dryland and irrigated farmlets at the Flaxley Agriculture Centre in South Australia where the areas of each were~30 and 16 ha each, respectively, at a wide range of stocking rates (Valentine et al 2009).…”
mentioning
confidence: 99%